A Simple Method for the Assessment of Fusarium Head Blight Resistance in Korean Wheat Seedlings Inoculated with Fusarium graminearum - Shin, Sanghyun; Kim, Kyeong-Hoon; Kang, Chon-Sik; Cho, Kwang-Min; Park, Chul Soo; Okagaki, Ron; Park, Jong-Chul (The plant pathology journal, 2014)
Fusarium head blight (FHB; scab) caused mainly by Fusarium graminearum is a devastating disease of wheat and barley around the world. FHB causes yield reductions and contamination of grain with trichothecene mycotoxins such as deoxynivalenol (DON) which are a major health concern for humans and animals. The objective of this research was to develop an easy seed or seedling inoculation assay, and to compare these assays with whole plant resistance of twenty-nine Korean winter wheat cultivars to FHB. The clip-dipping assay consists of cutting off the coleoptiles apex, dipping the coleoptiles apex in conidial suspension, covering in plastic bag for 3 days, and measuring the lengths of lesions 7 days after inoculation. There were significant cultivar differences after inoculation with F. graminearum in seedling relative to the controls. Correlation coefficients between the lesion lengths of clip-dipping inoculation and FHB Type II resistance from adult plants were significant (r=0.45; P<0.05). Results from two other seedling inoculation methods, spraying and pin-point inoculation, were not correlated with adult FHB resistance. Single linear correlation was not significant between seed germination assays (soaking and soak-dry) and FHB resistance (Type I and Type II), respectively. These results showed that clip-dipping inoculation method using F. graminearum may offer a real possibility of simple, rapid, and reliable for the early screening of FHB resistance in wheat.